Emojified communication: How do news organizations use emojis on social media? - Ahmed Al-Rawi (Telematics and Informatics Reports)
In this paper, a largely under-researched area of news study is explored which is the use of emojis by news organizations. Though emoticons and then emojis have been part of social media since the beginning, there is little empirical and theoretical research on this aspect of news. A new conceptualization of this digital phenomenon is introduced which is called “emojified communication”. Situated within Semiotics theory, it is defined as a means of communicating nonverbal meaning to complement the main media content, and it serves in offering contextual insight and enriching the message’s cognitive and emotional cues. Using a mixed method approach, the results show that when it comes to emojified news, news organizations predominately use various people’s icons and positive sentiments, creating relatable and lively posts that can enhance the news items’ emotional appeals and cognitive cues. To target certain audiences, news organizations used emojis that showcased women slightly more than those that referenced men, while light skin colors were used much more than darker ones. The paper concludes with a discussion on the possible drawbacks of using emojis in news branding.